Economic impacts of hosting the winter olympics on GDP per capita - Žečkytė, Aistė (Lithuanian Journal of Statistics, 2022)
The Winter Olympics have been held since 1924, and each time host countries spend billions on organization, so it is important for them to know if this pays off in the future. This paper examines whether hosting the Winter Olympic Games yields long-term economic benefits. To achieve this, the difference-in-difference model for relative changes in Gross Domestic Product per capita was estimated. A difference-in-difference estimator examines post-Olympic impacts for host countries between 1972 and 2014. Regression results provide no additional long term impacts of hosting the Winter Olympics on GDP per capita.
Keywords: Winter Olympics; difference-in-difference; Gross Domestic Product; economic growth; long-term